Correlates of Adiponectin in Hepatitis C–Infected Children. Issue 2 (February 2015) - Delgado-Borrego, Aymin; Gonzalez-Peralta, Regino P.; Raza, Roshan; Negre, Betania; Goodman, Zachary D.; Jonas, Maureen M.; Chung, Raymond T.; Ludwig, David A.
ABSTRACT Objectives: Adiponectin is a regulator of cytokines that, in turn, play a vital role in inflammatory and immune responses. Adiponectin is therefore likely to have a contributory role in hepatitis C virus (HCV) infection. We sought to characterize adiponectin levels and examine correlates in a pediatric HCV-infected cohort. Methods: We performed a cross-sectional study in children (5–17 years of age, n = 86) in the Pediatric Study of Hepatitis C (PEDS-C) trial. Adiponectin levels were univariately correlated with patient demographics, anthropometrics, and viral and histological measures. Multivariate regression models were used to identify the unique (ie, nonconfounded) associations with adiponectin concentrations. Results: Body mass index (BMI) had the highest univariate inverse correlation with loge adiponectin (r = −0.5, P < 0.0001). In multivariate analysis, BMI remained inversely correlated with loge adiponectin after accounting for age and route of HCV transmission (r = −0.38, P = 0.0003). Steatosis and fibrosis were inversely related to loge adiponectin in univariate analysis, but these associations were not statistically significant after multivariate adjustments (P ≥ 0.1827). Conclusions: High BMI among HCV-infected children is associated with lower adiponectin levels. Practitioners should be cognizant of the possible risks of low adiponectin when managing HCV-infected children who are overweight. Further studies are indicated to determine the impact of having low adiponectin on HCV infection in youth.